The Red Danger in Brazilian cinema: the narratives of political exiled people and ex-prisoners of the military dictatorship in the contemporary documentary - Tomaim, Cássio dos Santos (2010)
In the first decade of 2000 the Brazilian cinema demonstrated a growing interest in portray in the screens episodes of the military dictatorship in the country, rummaging through hurts, complex and painful subject of our past. What for some military men was a revenge of the communists or of the Brazilian political left that would have invaded the Brazilian media. This way, starting from the analyzes of the Vlado, 30 years later (2005), Hércules 56 (2006) and Caparaó (2006) movies, we intended to point some initial reflections about how the contemporary Brazilian documentary, when update the past of the military dictatorship from a ethical and political compromise with the memory of the ones who participated of the armed fight in the country, struggle a esthetical fight against the forgetfulness and the denial of a dark period of the recent Brazilian history.